2004
DOI: 10.1007/s11745-004-1258-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering and applications of Candida rugosa lipase isoforms

Abstract: Commercial preparations of Candida rugosa lipase (CRL) are mixtures of lipase isoforms used for the hydrolysis and synthesis of various esters. The presence of variable isoforms and the amount of lipolytic protein in the crude lipase preparations lead to a lack of reproducibility of biocatalytic reactions. Purification of crude CRL improve their substrate specificity, enantioselectivity, stability, and specific activities. The expression of the isoforms is governed by culture or fermentation conditions. Unfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 86 publications
3
71
1
2
Order By: Relevance
“…In addition, it possesses stereoselectivity and regioselectivity ability for the synthesis of pharmaceuticals, glycoderivatives and carbohydrate esters used in the manufacture of many foods and fragrances [Akoh et al, 2004]. Previously, several li-pase genes with high homology (between 60 and 70%) had been cloned from C. rugosa, namely lip1 to lip7 [Longhi et al, 1992;Lotti et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it possesses stereoselectivity and regioselectivity ability for the synthesis of pharmaceuticals, glycoderivatives and carbohydrate esters used in the manufacture of many foods and fragrances [Akoh et al, 2004]. Previously, several li-pase genes with high homology (between 60 and 70%) had been cloned from C. rugosa, namely lip1 to lip7 [Longhi et al, 1992;Lotti et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, esterases in general are attractive tools for biocatalytic applications, such as chiral synthesis of pharmaceuticals or agrochemicals (17). Recently, several bacterial esterases have been subjected to laboratory evolution to obtain enzymes with improved properties, including substrate specificity or enantioselectivity (2,33,35). The primary aim of the present study was to combine the advantages of cellular surface display with the attractive features of a bacterial esterase (4).…”
mentioning
confidence: 99%
“…The commercial lipase isoform mixtures prepared from Candida rugosa meet this requirement. Obtaining pure and different C. rugosa lipase isoforms is possible by means of computer modelling of lipase isoforms, and protein engineering methods such as lid swapping and DNA shuffling (Akoh et al, 2004). A recent review on microbial lipases focused on non-aqueous microbial lipase catalysis and major factors affecting esterification/transesterification processes in organic media.…”
Section: Application Name Example Reference(s)mentioning
confidence: 99%
“…Screening organic solvent-tolerant bacteria or extremophiles has been preferred to isolate and improve naturally solvent-stable enzymes (Gupta & Khare, 2009;Doukyu & Ogino, 2010). Other protein engineering examples with industrially and/or pharmacologically important enzymes include studies on cholesterol oxidase (Pollegioni et al, 2009), cyclodextrin glucanotransferases (Leemhuis et al, 2010), human butyrylcholinesterase (Masson et al, 2009), microbial glucoamylases (Kumar & Satyanarayana, 2009), lipases of different origins (Akoh et al, 2004;Verma et al, 2008;Kurtovic et al, 2009), phospholipases (Song et al, 2005;De Maria et al, 2007;Simockova & Griac, 2009) and phytases (Rao et al, 2009). Studies on extremozymes, enzymes isolated from extremophilic species, revealed their different structural and functional characteristics which could be exploited for biotechnological applications and improved further by protein engineering (Bjarnason et al, 1993;Hough & Danson, 1999;Georlette et al, 2004).…”
Section: Applications With Various Industrially Important Enzymesmentioning
confidence: 99%